Clinical, Radiometabolic and Immunologic Effects of Olaparib in Locally Advanced Triple Negative Breast Cancer: The OLTRE Window of Opportunity Trial - Schettini, Francesco; Corona, Silvia Paola; Giudici, Fabiola; Strina, Carla; Sirico, Marianna; Bernocchi, Ottavia; Milani, Manuela; Ziglioli, Nicoletta; Aguggini, Sergio; Azzini, Carlo; Barbieri, Giuseppina; Cervoni, Valeria; et al. (Frontiers in Oncology, 2021)
Introduction Olaparib is effective in metastatic triple negative breast cancer (TNBC) carrying germline mutations in DNA damage repair (DDR) genes BRCA1/2 (gBRCA-mut). The OLTRE window-of-opportunity trial preliminarily investigated potential pathologic, radiometabolic and immune biomarkers of early-response to olaparib in gBRCA-wild-type (wt) TNBC and, as proof-of-concept in gBRCA-mut HER2-negative BC. Methods Patients received olaparib for 3 weeks (3w) before standard neoadjuvant chemotherapy and underwent multiple FDG18-PET/CT scan (basal, after olaparib), clinical assessments (basal, every 3w), tumor biopsies and blood samplings (baseline, after olaparib). Clinical and radiometabolic responses were evaluated according to RECIST1.1 and PERCIST criteria. Results 27 patients with gBRCA-wt TNBC and 8 with gBRCA-mut BC (6 TNBC, 2 HR+/HER2-negative) were enrolled. Three (11.1%) patients showed mutations in non-BRCA1/2 DDR genes and 4 (14.8%) in other genes. 3w olaparib induced 16/35 and 15/27 partial clinical and radiometabolic responses, including in 40.7% and 50.0% gBRCA-wt patients. gBRCA-mut tumors presented numerically higher tumor-infiltrating lymphocytes (TILs) levels and PD-L1 positive tumors. Clinical responders experienced a reduction in T-regs/T-eff ratio (p=0.05), B and NK lymphocytes (p=0.003 both), with an average increase in T-helpers rate (p<0.001) and CD4/CD8 ratio (p=0.02). Ki67% and TILs did not vary significantly (p=0.67 and p=0.77). A numerical increase in PD-L1 positive cases after olaparib was observed, though non-significant (p=0.134). No differences were observed according to gBRCA status and type of response. Conclusions Early-stage TNBC might be a target population for olaparib, irrespective of gBRCA mutations. Future trials should combine TILs, PD-L1 and gBRCA status to better identify candidates for escalated/de-escalated treatment strategies including olaparib.